Scenarios Practices: In Search of Theory - Wilkinson, A (2009)
Graham Molitor's article provides a timely prompt for reflecting on the value of scenario practices, especially given several data sources indicating their usage has increased significantly since 2001 (e.g. Ramirez, Selsky, & van der Heijden, 2008, p.9). Molitor is not alone in his struggle to clarify the effectiveness of scenario practices. Others, including myself, are endeavouring to address similar questions: how to judge effectiveness and what do we mean by 'effectiveness' when referring to such practices? As he implicitly suggests, his critique does not imply that we should throw the scenario 'baby out with the bathwater'. It is all too easy to agree with some of the criticisms of scenarios raised by Molitor. Three aspects are particularly relevant: The first is that futures work seems to be characterised by highly personalised practices. Such practices can be introduced by someone who thought it was "a good idea" but who failed to fully reflect on the complexity of the situation and bases their choice of techniques on sound theoretical principles. Secondly, as much of scenario work is secret – particularly in military and corporate sectors- and/or difficult to assess, it is very hard to engage in comparative research. Thirdly, common to other practitioner-led fields, scenario practices are blessed with a high degree of innovation and entrepreneurship and cursed by a lack of reliable accounts that render explicitly what has worked and what has not, why and for whom in different settings. In the limited space available, however, I would like to raise three areas that I feel are worthy of further reflection: